2014
DOI: 10.1371/journal.ppat.1004336
|View full text |Cite
|
Sign up to set email alerts
|

A Cysteine Protease Inhibitor of Plasmodium berghei Is Essential for Exo-erythrocytic Development

Abstract: Plasmodium parasites express a potent inhibitor of cysteine proteases (ICP) throughout their life cycle. To analyze the role of ICP in different life cycle stages, we generated a stage-specific knockout of the Plasmodium berghei ICP (PbICP). Excision of the pbicb gene occurred in infective sporozoites and resulted in impaired sporozoite invasion of hepatocytes, despite residual PbICP protein being detectable in sporozoites. The vast majority of these parasites invading a cultured hepatocyte cell line did not d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…TRAP itself is likely cleaved by an intramembrane protease of the rhomboid family and this cleavage is important to achieve continuous migration (Ejigiri et al 2012). Moreover, an inhibitor of cysteine proteases is necessary for sporozoite motility, and icpsporozoites reproduce the life-cycle arrest observed in trap --infected mosquitoes (Boysen and Matuschewski 2013;Lehmann et al 2014).…”
Section: Sporozoite Gliding Motility Trap Family Adhesins and Actinmentioning
confidence: 99%
“…TRAP itself is likely cleaved by an intramembrane protease of the rhomboid family and this cleavage is important to achieve continuous migration (Ejigiri et al 2012). Moreover, an inhibitor of cysteine proteases is necessary for sporozoite motility, and icpsporozoites reproduce the life-cycle arrest observed in trap --infected mosquitoes (Boysen and Matuschewski 2013;Lehmann et al 2014).…”
Section: Sporozoite Gliding Motility Trap Family Adhesins and Actinmentioning
confidence: 99%
“…We propose that SUB1-ProM may play such a regulatory role in the PV or at the intracellular merozoite surface (which is effectively exposed to the contents of the PV lumen). This would be by no means unprecedented; endogenous protease inhibitors are widespread in biological systems, where they often play crucial roles, and although protein-based peptidase inhibitors are relatively sparse in prokaryotes and unicellular eukaryotes [59], they have previously been identified in the malaria parasite for other peptidase classes [60][61][62]. Our finding that the PfSUB1 and PvSUB1 propeptides were the best templates for homology modelling of SUB1-ProM may indicate an evolutionary adaptation of SUB1-ProM to optimally mimic these propeptides in order to perform its regulatory function.…”
Section: Discussionmentioning
confidence: 99%
“…The investigators concluded that sporozoites motility is crucially required for salivary gland invasion and exoerythrocytic stages. Sporozoites require more motility and time to reach their target in mosquitoes and exoerythrocytic location rather than intra-erythrocytic stages, and that is where effects of CYS down regulation were more apparently observed [155] .…”
Section: [Iii] Cystatins (Cyss)mentioning
confidence: 99%
“…Interestingly, only the 11 kDa C-terminal region of FP-2 prodomain was found essential for efficient FP-2 regulation and inhibition. In addition, structure-function studies demonstrated that only a small portion of the prodomain C terminal (leucine 155 asparagine 216 ) was sufficient for inhibition of the mature FP-2 [17] . Three other studies reported similar results [18][19][20] , and accordingly, further studies to develop new anti-malarial drugs based on FP-2 motif of its C terminal were recommended.…”
mentioning
confidence: 99%